Distribution Pattern Analysis and Marketing Margins Rabbitfish Fish in Pangkajene District and Islands - Murtini, Murtini; Ibrahim, Muhammad Akmal; Harianti, Harianti; Dananjaya, Wayan Kantun (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
The price of Rabbitfish fish at the consumer level for each region is quite different. This study aims to analyze distribution patterns and marketing margins of Rabbitfish fish. This research is classified as a qualitative type with a survey method by distributing questionnaires. Respondents consisted of 20 fishermen, 20 collectors, 15 retailers and 5 consumers and 5 restaurants. The results of this study indicate that there are four distribution patterns, namely (1) direct fishermen to final consumers, (2) fishermen to collectors to final consumers, (3) fishermen to collectors, to retailers to final consumers and (4) fishermen to collectors, to wholesalers, to retailers, to final consumers. The marketing margin on the first marketing channel is IDR 5,000/kg, the second is IDR 5,000/kg, the third is IDR 15,000/kg and the fourth is IDR. 20,000/kg. The longer the marketing channel, the higher the margin earned.